2017
DOI: 10.1002/joc.5165
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of variability and trends of precipitation extremes in Singapore during 1980–2013

Abstract: Changes in precipitation extremes in the tropical urban context is complex, where the precipitation activities are influenced by the combined effects of El Niño-Southern Oscillation (ENSO), global warming and local effects. This study presents a comprehensive framework to investigate the variability and trends in precipitation extremes in a tropical urban city-state, Singapore, based on a set of extreme indices recommended by the Expert Team on Climate Change Detection and Indices (ETCCDI). The long-term trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 45 publications
5
79
1
1
Order By: Relevance
“…Increasing trends in R10mm and R20mm indices are detected at most of the evaluated stations, as shown in Figure 5b,c, respectively. The current study found that the number of extreme precipitation days are increasing over the MRB, which is in agreement with those obtained in nearby regions, i.e., Singapore [6] and Kelantan River Basin [14]. The regional trend in CDD decreased with a magnitude of 2.69 days/decade, meanwhile CWD increased at a rate of 0.1 days/decade.…”
Section: Annual Trend Of Precipitation Extremessupporting
confidence: 91%
See 2 more Smart Citations
“…Increasing trends in R10mm and R20mm indices are detected at most of the evaluated stations, as shown in Figure 5b,c, respectively. The current study found that the number of extreme precipitation days are increasing over the MRB, which is in agreement with those obtained in nearby regions, i.e., Singapore [6] and Kelantan River Basin [14]. The regional trend in CDD decreased with a magnitude of 2.69 days/decade, meanwhile CWD increased at a rate of 0.1 days/decade.…”
Section: Annual Trend Of Precipitation Extremessupporting
confidence: 91%
“…In contrast to some Southeast Asia studies [6,25] that indicated tendency of wetter conditions due to increasing R95p and R99p trends, the MRB experienced drier conditions in the period of 1985-2015. This is proven through the reduction of precipitation amount contributed by the extremely wet days.…”
Section: Annual Trend Of Precipitation Extremescontrasting
confidence: 75%
See 1 more Smart Citation
“…El Niño-Southern Oscillation (ENSO) is the main global driver of fluctuations in tropospheric moisture content (Trenberth et al 2005), a key ingredient for extreme rain, and its influence is most pronounced in the tropics (Trenberth 2011). Recent efforts in attributing observed changes in tropical region precipitation extremes to mixed influence from local processes, ENSO, and global change (Li et al 2016(Li et al , 2018 provide helpful guidance for similar work in SSA.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of an urban heat island (UHI), for example, has particularly strong implications for outdoor thermal comfort and health in a tropical context where air temperatures and humidity are already high throughout the year. A similar important question is to what extent the increase in the number of heavy rainfall events observed during the last 20 years in Singapore (Li et al, 2018) can be attributed to enhanced convection and emissions of aerosols, an issue which is of general relevance. Many observational studies are available to inform about individual aspects of the urban atmosphere.…”
Section: Introductionmentioning
confidence: 99%